Templating Hip Arthroplasty - Alnahhal, Amro (Open Access Maced J Med Sci, 2019)
BACKGROUND: Different methods have been developed and employed with variable degrees of success in pre-operative templating for total hip arthroplasty. Preoperative templating, especially digital templating, has been claimed to have increased the effectiveness of total hip arthroplasty by improving the precision of prediction of prosthetic implant size. AIMS: The overall aim of this systematic review is to identify whether the use of pre-operative templating in total hip arthroplasty procedures has resulted in increased accuracy, reliability and precision of the procedure. Various methods of templating, like traditional acetate overlay and digital method of templating that includes a single radiographic marker and double radiographic marker methods, have been compared to establish the most reliable method of templating. METHODS: We searched the PubMed, Google Scholar Cochrane Central Register of Controlled Trials (CENTRAL), and MEDLINE (1966 to present), EMBASE (1980 to present), CINAHL (1982 to present), Psych INFO (1967 to present) and Clinical Trials Gov. CONCLUSION: The results of this systemic review suggest that preoperative templating is resulting in an enormous increase in the accuracy of total hip arthroplasty and among various methods, King Mark is the most reliable method.